Assessment of Drinking Water Quality and Willingness to Pay for its Quality Improvement in Chitre, Parbat, Nepal - Regmi, Sarala; Chapagain, Prem Sagar; Magar , Yogesh Rana (Journal of Nepal Chemical Society, 2025)
The study was conducted in Chitre village, Panchase area. Water samples from springs, reservoirs, and public taps were collected in April 2016, pre-monsoon season, to analyze various water quality parameters. A total of 17 samples were collected, comprising 9 from springs, 2 from reservoirs, and 6 from public taps. Parameters such as temperature, pH, electric conductivity, chloride, total alkalinity, total hardness, phosphate, ammonia, nitrate, iron and microbiological parameter i.e. total coliform were analyzed following the methods outlined in APHA. Contingent valuation method was used to examine the willingness to pay (WTP) of the respondents to improve drinking water quality. The physicochemical parameters results showed that all water sources had water quality within the permissible range as per Nepal Drinking Water Quality Standards (NDWQS-2006). Similarly, the microbiological analysis of water samples revealed the presence of total coliform in all samples and crossed the NDWQS. Therefore, the water was potable in terms of microbiological point of view in the study area only after disinfection. Contamination at the sources might be due to the lack of protection of springs, leakage in pipe distribution system and lack of proper cleaning of reservoirs. Of the 71 respondents, 97.18 % were willing to pay to improved drinking water quality. The computed mean willingness to pay amounts were NRs 59.95 per month per household. WTP was significantly related to the education, occupation, ethnicity, water quality perception and household water treatment practices. Study showed that there was a demand for an improvement in the drinking water quality.